Peningkatan Pengamalan Ibadah Shalat Siswa Melalui Kerjasama Guru dengan Orang Tua Wali di SMP Negeri 2 Talamau - Afni Rozi; Riki Saputra; Rahmi Rahmi (Jurnal Kajian dan Pengembangan Umat, 2020)
Prayer is the main obligation for Muslims, in carrying it out sometimes many people feel heavy without the exception of students in educational institutions. Along with the problem, strong cooperation between various parties is needed in fostering an avid generation of worship. This research will illustrate the cooperation between Islamic religious education teachers and parents of students in improving the prayer of students. To get the intended purpose, this research was designed in the form of qualitative research, while the place of research was conducted in Junior High School 2 Talamau West Pasaman Regency, the source of this research is teachers, parents and some students who are selected purposively. The data collection techniques used are observation, interview and study documentation. Based on the results of the study it is known that the cooperation between teachers and parents of students in conducting supervision to improve student worship is still running less smoothly, the reality is becoming clearer when the discovery of students who have not filled out prayer control documents issued by the school. However, according to the concept of cooperation that should be built between schools and parents has been successfully implemented in SMP Negeri 2 Talamau Pasaman Barat.